Strengthening Cash Waqf Literacy through National Regulations for Economic Empowerment - Ahmad Shobri (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2025)
This policy paper describes that cash waqf is a potential Islamic philanthropic instrument to support community development and sustainable economic empowerment. However, its implementation in Indonesia still faces major challenges, particularly the low level of public understanding, limited capacity of nazir (waqf managers), and the lack of technical re gulations and fiscal incentives. A survey by the Indonesian Waqf Board (BWI, 2023) shows that only about 23% of the population understands the concept of cash waqf. This condition hampers the optimal utilization of cash waqf to support national development agendas, including the Ministry of Religious Affairs' Strategic Plan 2025–2029 and the Sustainable Development Goals (SDGs). This study applies a qualitative approach through document analysis, literature review, and comparison with international practices in Malaysia and Turkey. The analysis employs theories of Islamic financial literacy, institutional theory, and trust theory in Islamic philanthropy. The findings indicate that improving public literacy is the most urgent policy to implement, as it serves as the entry point for strengthening nazir capacity and regulatory reform. The main recommendation is the establishment of a Ministerial Regulation (PMA) on Cash Waqf Literacy, covering curriculum integration, digital literacy campaigns, involvement of mosques and Islamic organizations, and national evaluation mechanisms. This policy is expected to increase public understanding to at least 50% by 2029, expand the number of waqf donors, strengthen nazir capacity, and position cash waqf as a sustainable financing instrument for community economic development.